Overlapping and specific bacterial communities in the gut and reproductive system of Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) adults - Li, Wei-Jun; Hu, Kai-Ping; Zhong, Xin; Song, Shui-Lin; Xu, Cui-Kang; Xie, Qing-Xiu; Li, Xiao-Zhen (Frontiers in Microbiology, 2025)
BackgroundDifferent insect tissues represent heterogeneous niches with distinct physiological and biochemical characteristics, and therefore host different bacterial communities.MethodsIn this study, those overlapping and specific bacterial communities in the female gut (fG), male gut (mG), female reproductive system (fR), and male reproductive system (mR) of Bactrocera dorsalis (Hendel) adults were determined by high-throughput sequencing targeting 16S rRNA gene.ResultsThe richness of bacterial taxa based on OTU was higher in fR compared to the other three tissues. Among the 29 identified bacterial phyla, Pseudomonadota, Bacillota, and Bacteroidota were predominant, while among the 48 identified genera, Enterobacter, Kluyvera, Asticcacaulis, Mesorhizobium, and Serratia were common in the four tissues. fG harbored specific bacterial genus Morganella, mG harbored specific bacterial genera Vagococcus, Lactobacillus, Lactococcus, Lactobacillales, and Bacilli, fR harbored specific bacterial genera Blastomonas, Ralstonia and Providencia, and mR harbored specific bacterial genera Sphingobacteriia, Asticcacaulis, Caulobacter, Caulobacterales, Bradyrhizobium, and Luteimonas. In the 35 annotated KEGG pathways, high-abundance bacterial taxa were mainly enriched in these pathways of membrane transport, carbohydrate metabolism, amino acid metabolism, replication and repair, and energy metabolism, while low-abundance bacterial taxa were involved in these pathways of cardiovascular diseases, circulatory system, and excretory system. The abundances of the 5 pathways associated with cardiovascular diseases, circulatory system, excretory system, membrane transport, and polysaccharide biosynthesis and metabolism exhibited greater variations among fG, mG, fR, and mR. Among them, the two pathways abundances of cardiovascular disease and circulatory system were higher in the reproductive system, whereas the other three pathways abundances were higher in the female gut.ConclusionOur study revealed the abundance, composition and function of overlapping and specific bacterial communities in the gut and reproductive system of B. dorsalis, providing valuable information for inhibiting the occurrence of B. dorsalis by interfering with these functional bacterial communities in tissues.